Does social distrust always lead to a stronger support for government intervention? - Hans Pitlik; Ludek Kouba (WWWforEurope, 2014)
We address empirically trust as a determinant of support for government intervention. The central notion provided in the present paper is that the influence of generalized social trust on intervention attitudes is conditional on the perceived reliability, honesty, and incorruptibility of state actors and of major companies. Starting point is an idea by Aghion, Algan, Cahuc, and Shleifer (2010) that individuals who generally distrust others have a stronger taste for a regulation of economic activities, while people with high interpersonal trust are in favor of less strict regulations and state control. This line of argumentation neglects that (lack of) trust spills over to distrust in both governmental as well as in private institutions. People who tend to (dis-)trust other unknown people also tend to (dis-)trust state actors and private sector actors. Estimating the determinants of interventionist preferences with data from the World Values Survey/European Values Study for approximately 100,000 -115,000 individuals in 37 OECD- and EU-countries, we show that the impact of social trust on government intervention attitudes is conditional on individual confidence in state actors and in companies.
Keywords: D70; D78; H10; 330; Social trust; institutional trust; government regulation; preference formation